The National List of Essential Medicines of India 2022 (NLEM 2022): Tommy, Toe the Line - S. Manikandan (Elsevier, 2023)
Summary: India recently released its fifth National List of Essential Medicines 2022 (NLEM 2022). A critical analysis of the list was performed and was compared with the WHO 22nd Model List of Essential Medicines published in 2021. The Standing National Committee, since its inception, have taken four years to finalise a list. The analysis identified that all the available formulations and strengths of the selected drugs are included in the list, which must be avoided. Furthermore, the antibacterial agents are not categorised as access, watch and reserve (AWaRe) and this list is not aligned with the national programs, standard treatment guidelines and nomenclature. There are a few factual errors and some typographic errors. These problems in the list need to be rectified immediately so that the document would be able to serve the community more effectively as a true model list.